ASSESSMENT OF GROUNDWATER POLLUTION AROUND TORBALI, IZMIR, TURKEY - Aksoy A.O.; Scheytt T. (My University, 2007)
Torbali region is located near Izmir, Turkey. Industrial activities in this region have been developing from last two decades. The untreated industrial effluents discharged into the Fetrek River causes groundwater pollution in the region. Since groundwater resources of the region are used for drinking, agricultural and industrial purposes the groundwater quality assessment is done by analyzing the concentrations of main cations (Na+, K+, Ca2+, Mg2+) and anions (Cl-, SO 4 2-, NO 3 -, HCO 3 - ). Additionally, physical and chemical parameters (EC, total hardness, Eh, O 2 and pH) were determined. The results show that the concentrations are generally within drinking-water limits. Only the results of TDS and EC concentrations exceed the permissible limits for drinking water in the industrial belt of the region, while NO 3 - values exceed the permissible limits in the vicinity of the agricultural area. Concentrations are expected to increase in the next years as no effective sewage collection and treatment is in place. © 2007 Springer-Verlag.
Keywords: CONTAMINATION; GROUNDWATER; TORBALI; TURKEY